Transparência pública e desenvolvimento humano: uma análise dos portais de transparência de municípios da Região Metropolitana de São Paulo - Casemiro, Gabriel Banqueri (2024)
Considering the Brazilian democratic context, based on the Federal Constitution of 1988 and its consequences for Public Administration, and also the proposal for a more modern, more demanding public management and civil society, more engaged in issues related to public governance and public transparency, especially based on the Fiscal Responsibility Law of 2000, the Transparency Law of 2009 and the Access to Information Law of 2011, the general objective of this study is to analyze whether there is a diachronic dialectical relationship between the Mandatory Information Disclosure Index (IDIO) of the Transparency Portals of the Municipal Governments of the Municipalities of the Metropolitan Region of São Paulo (RMSP) and the Municipal Human Development Index (IDH-M) of the Municipalities that make up this metropolitan region of São Paulo. To this end, this work is developed in three stages: first, by carrying out bibliographical and documentary research on the following themes: 1. Agency Theory, Corporate Governance and Public Governance; 2. Public Transparency, Digital Information and Communication Technologies (TDICs) and Transparency Portals; 3. Development, Human Development and their Indicators: GDP, HDI and HDI-M; in the second part, the data related to mandatory disclosure information found in the Transparency Portals of the Municipalities of the RMSP are observed, described and quantified, using a model adapted from the Mandatory Disclosure Observation Form for Transparency Portals, proposed by Fabre (2017); and, in the third part, the IDIOs and HDI-Ms of the RMSP are observed, qualified, analyzed and compared, in order to prove the hypothesis that there is a diachronic dialectical relationship between the regional level of active transparency of information (mandatory disclosure) expressed by the Transparency Portals of the Municipalities of the region and the level of human development expressed by the regional HDI-M. The results of the research point to the confirmation of a diachronic dialectical relationship between the level of transparency and the level of human development, which occurs, however, based on the tendency of the level of transparency to follow and be equivalent, over time, to the level of human development, when the context is of high or very high HDI-M.